Optimization of the Preparation Conditions of Polyaluminum Chloride by Recycling of Cans - habeb, anwer; Al-Hilli, Muthafar F. (Iraqi Journal of Physics, 2025)
This study involved the preparation of polyaluminum chloride (PAC) from basic materials and elements, namely aluminum flakes (pure and impure), by dissolving them in hydrochloric acid diluted to 50%. The flakes were added gradually to ensure the formation of a PAC solution with high specifications and efficiency in treating turbid water and forming heavy flocs as one of the important applications for removing turbidity and some elements from drinking water and wastewater. This method was verified using a turbidity meter and the application mechanism using a jar-test apparatus. The analyses showed that the efficiency and sedimentation speed reached 95% for high turbidity levels and 98% for low turbidity levels. X-ray diffraction (XRD) analyses clarified the compounds present in both pure and impure materials, and the purity of the material was determined using a UV device. The results indicated the purity of the substance in the solution prepared from pure materials and the level of impurities in the solution prepared from impure materials (poly aluminum), as well as the efficiency variation according to the alkalinity of the solution. Additionally, Fourier Transform Infrared (FT-IR), an atomic absorption spectrometer, and a titration meter for chlorine measurement were used. The comparison between PAC and alum showed the potential of PAC as an ideal and highly efficient alternative.